The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1371/journal.pone.0234286
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological study on foot-and-mouth disease in small ruminants: Sero-prevalence and risk factor assessment in Kenya

Abstract: Foot-and-mouth disease (FMD) is endemic in Kenya affecting cloven-hoofed ruminants. The epidemiology of the disease in small ruminants (SR) in Kenya is not documented. We carried out a cross-sectional study, the first in Kenya, to estimate the sero-prevalence of FMD in SR and the associated risk factors nationally. Selection of animals to be sampled used a multistage cluster sampling approach. Serum samples totaling 7564 were screened for FMD antibodies of non-structural-proteins using ID Screen® NSP Competiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
3
1
Order By: Relevance
“…These findings were in line with the outcomes of Balinda et al [ 45 ], who investigated that the cause of the infection and spread of FMD was the closed interface among livestock in communal grazing and joint housing. Though, the finding of the present investigation is contrary to the outcomes of Chepkwony et al [ 46 ], who investigated that, only mixed production systems indicated a statistically positive relationship with FMD seropositivity, while other production systems, including nomadism and transhumance, showed a significant negative association with FMD seropositivity. It might be due to sampling size, farming method, animal management system, climate factors, and study area differences.…”
Section: Discussioncontrasting
confidence: 99%
“…These findings were in line with the outcomes of Balinda et al [ 45 ], who investigated that the cause of the infection and spread of FMD was the closed interface among livestock in communal grazing and joint housing. Though, the finding of the present investigation is contrary to the outcomes of Chepkwony et al [ 46 ], who investigated that, only mixed production systems indicated a statistically positive relationship with FMD seropositivity, while other production systems, including nomadism and transhumance, showed a significant negative association with FMD seropositivity. It might be due to sampling size, farming method, animal management system, climate factors, and study area differences.…”
Section: Discussioncontrasting
confidence: 99%
“…In Kenya, NSP ELISA national seroprevalence was recorded from 52.5% to 93% in different areas of the country [42][43][44] in cattle, whereas in small ruminants [45], 22.5% seroprevalence was documented by NSP ELISA. In swine, the seroprevalence using NSP ELISA was reported to be 54.4% [46], whereas in African buffalo, 77% seroprevalence was reported in Kenya by Omondi et al [44] using NSP ELISA.…”
Section: Distribution and Overall Prevalence Of Foot-and-mouth Diseas...mentioning
confidence: 99%
“…Foot-and-mouth disease virus (FMDV) is the etiological agent responsible for foot-and-mouth disease (FMD) in cloven-hoofed livestock 1 . In livestock, the FMD is characterized by acute fever with formation of vesicles in the oral cavity and feet 2 , 3 . The aftereffects of this disease include loss of appetite and body weight, decreased milk yield, decreased draft power, abortions, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This necessitates advanced statistical methods and tools for estimating the sero-prevalence rate at population-level using test results from NSP-ELISA. However, attempts have been made to estimate the FMDV sero-prevalence through cross sectional sample-based sero-surveillance in cattle 29 , 33 , 34 and small ruminants 29 in Ethiopia, cattle and wild life in Nigeria 35 , wild life and buffalo population in eastern Africa 36 , small ruminants in Kenya 2 , etc. In all these studies, the sero-prevalence results were limited to sample proportions (e.g., total sample: 384; positive sample: 76; sero-prevalence rate: 19.79%) 29 , 33 36 without going for country-level estimate of FMDV sero-prevalence rate.…”
Section: Introductionmentioning
confidence: 99%